A case study on the potential benefits of using expanded polystyrene geofoam to mitigate seismic impact on structures - Hasan Muhommed Ashiq; Shadman Rahman Sabab; Mozaher Ul Kabir; Chowdhury Zubayer Bin Zahid; Md Rahat Hassan (Hybrid Advances)
Expanded Polystyrene (EPS) geofoam has been utilized in construction in a wide range of countries for years. EPS serves as a compressible buffer between the soil and the structure itself. It absorbs a significant percentage of the static and dynamic stresses induced by earthquake-loaded soil. Because Bangladesh is prone to earthquakes and Chittagong is a high seismic risk zone, the use of EPS in buildings could be a great solution for decreasing seismic damage. In this study, the impact of implementing EPS as a compressible buffer around the substructure on Chittagong soil against seismic load was investigated using Plaxis3D software to generate a finite element model. The study compared two scenarios, one with and one without EPS 15 put around the structure's basement, to examine the impact of an earthquake on a five-story building. The wave oscillation graphs that were generated were used to build the energy (J) vs time (s) graphs to compare the findings. The results reveal that applying EPS 15 allows for better energy dissipation over time than without it, indicating that EPS has the potential to decrease seismic damage to a structure.